The Construction and Application of a Metaverse Teaching Space in the Context of Online Learning - Yuhui Yang; Hao Zhang; Jing Yuan; Qingyuan Yang; Yan Jiang; Lixia Chen (International Journal of Computer Games Technology)
With the accelerated development of digital education, traditional online teaching methods face challenges in providing immersive and interactive experiences. This study addresses these challenges by designing a metaverse teaching space architecture, integrating key learning theories to explore its potential in enhancing the quality of online education. This framework has been applied at Zhejiang University (ZJU), developing the “Learning in ZJU” metaverse teaching space, which supports innovative activities such as online teaching and academic seminars. Through questionnaire surveys, SPSS software data analysis, and SWOT analysis, the research shows that the metaverse teaching space significantly enhances immersive learning experiences, student engagement, and richness of instructional resources and promotes collaborative learning among students. Simultaneously, it faces challenges such as technological barriers, the need to enhance teachers’ information literacy, and cybersecurity issues. This study provides a reference for other educational institutions to explore and implement the metaverse teaching space and its applications, highlighting its enormous potential in personalized learning and stimulating students’ interest in learning. In the future, the metaverse teaching space is expected to become a key component of online education, but ongoing attention to technological advancement and educational innovation is necessary to overcome existing challenges.